Digital rain gauge - Mohd Firdhaus, Samah (2008)
Rain fall is nature phenomena that occur that give humidity on the ground. Too much humidity cause flood on the ground and if the humidity is small, the ground is dry. The rain gauge is the equipment that used by people in weather station to measure cumulative rain fall at a given location and given time. Rain gauge also known as udometer or pluviometer consist main part can to collect water fall from funnel above it, and outer case to protect the inner can. The new design of rain gauge give more accurate reading now day and have many other advantage such as observer can observe the rain fall from far, the measure of rain fall is according tip drop not only looking at the water level anymore where is sometimes cause error, the digital reading can be taken and many more. Tipping Bucket Rain Gauge is the new device that has all the advantage of the criteria above. This rain gauge is using two small bucket acting like see-saw, when one of the buckets is fill with water it will spill because of the unbalance see-saw. Then the other bucket will fill the water and repeat the same action like the first bucket and keep repeating until the rain stop. With the combination of the Microcontroller, sensor and LCD, digital rain gauge is build.